ChemInform Abstract: Synthesis of Novel 2‐Oxoquinoline Derivatives via Ugi‐Four‐Component‐Heck Reaction. Issue 31 (August 2015) - Rasouli, Mohammad Ali; Mahdavi, Mohammad; Saeedi, Mina; Ranjbar, Parviz Rashidi; Shafiee, Abbas; Foroumadi, Alireza
Abstract Ugi coupling of 2‐bromoanilines with aromatic aldehydes, vinylacetic acid, and isocyanides followed by intramolecular Heck reaction of the Ugi adducts (V) provides the title compounds (VI) (11 examples) in good yield.